Modeling of Soil Losses on a Yellow Argisol Under Planted Forest - Guimarães,Danielle Vieira (2019)
ABSTRACT Erosion prediction models are a useful tool for soil use planning and soil conservation. This study aimed to apply the Universal Soil Loss Equation (USLE) in an experimental sub-basin located in the municipality of Teixeira de Freitas, in the southern end of the state of Bahia, Brazil. The following variables were calculated: rainfall erosivity factor, using the precipitation data; soil erodibility factor, by the correlation between erosivity and soil losses obtained from a standard plot installed in the field; topographic factor; vegetation cover and management factor; and conservation practices factor. The product of these factors corresponded to the soil losses in the sub-basin. Data from erosion plots were used to validate the model. The USLE predicted higher soil losses than that observed in the plots, and the eucalyptus proved to be efficient at reducing soil losses by erosion.